ANALISA TEMPAT PEMBUANGAN SAMPAH (TPS ) KECAMATAN MANUHING KABUPATEN GUNUNG MAS (Analysis Of Waste Disposal Place (Tps) Manuhing District, Gunung Mas Regency) - Tahan Tarif; Wandy , (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2021)
: Garbage is something that is always there in everyday life. Everyone who is active will produce waste and so is what happened in Manuhing District, Gunung Mas Regency. The problem of this research is that the waste management process that has been carried out has not been included in the good and correct category because the management process is carried out by improper disposal and by burning. The purpose of this study was to determine the existing waste management system in Manuhing District, Gunung Mas Regency. The research method used is qualitative research with a descriptive observational design. Research techniques carried out by means of field surveys, focus group discussions involving participants, open interviews, and literature studies. The participants used in this study were representatives from the Environment Agency, village heads, village representative bodies. The results of the study stated that the waste management in the sub-district was still not good, this was due to the absence of land for the construction of temporary shelters, the facilities and infrastructure that were still not good, and the level of public awareness that was still low on the importance of managing waste properly and correctly. Keywords: Environment, waste, waste management